Evaluation of Oil Palm Biomass Potential for Bio-oil Production via Pyrolysis Processes - Palamanit, Arkom; Shrivastava, Pranshu; Khongphakdi, Phornthip; Phusunti, Neeranuch; Tirawanichakul, Yutthana (International Journal of Integrated Engineering, 2020)
The yield and quality of bio-oil obtained from pyrolysis processes depends on many factors, including pyrolysis types, reactor types, operating conditions and biomass property. The objective of this work was therefore to evaluate the potential of oil palm biomass, including oil palm trunk (OPT), oil palm fronds (OPF), oil palm decanter (DC) and oil palm root (OPR) for producing bio-oil via pyrolysis processes. The potential of oil palm biomass was considered in terms of proximate analysis, ultimate analysis, heating value, equivalent heating value, Thermogravimetric analyser (TGA) and lignocellulose content. The results showed that the moisture content of fried samples was in the range of 7.5-10.7% (w.b), which was relatively low and appropriate for pyrolysis. The volatile content of OPT and OPF was higher than 72% (wt.). The carbon, oxygen and hydrogen content of oil palm samples were in the range of 41.5-45.6, 30.7-40.2 and 5.7-5.9% (wt.), respectively. The higher heating value (HHV) of samples was relatively low compared to the HHV of fossil fuels. The OPT and OPF had high cellulose and hemicellulose content, while provided low lignin content compared to the lignin content of DC and OPR. The TGA results showed that thermal decomposition of samples took place within the range of 200â€“450 Â°C, which the lignin content affected the thermal decomposition trend. These results revealed that the selected oil palm biomass had relatively high potential for producing bio-oil via pyrolysis processes, particularly the OPT and OPF.